Assocıatıon of serum urıc acıd level wıth dısease severıty and clınıcal outcomes ın COVID-19 - Oruc, Meric; Batirel, Ayse (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is likely to cause uric acid dysregulation, resulting in abnormal serum uric acid concentrations. In this study, we aimed to evaluate the associations between admission serum uric acid levels and demographic, clinical and laboratory features of patients hospitalized with Coronavirus disease 2019 (Covid-19) and to explore the effect of admission serum uric acid values on clinical outcomes. Methods. In this retrospective study, the demographic, clinical and laboratory data of patients with confirmed Covid-19 were collected from the electronic health records of the hospital. The study population was stratified according to the quartiles of serum uric acid; Quartile 1: ≤ 3.5 mg/dl, Quartile 2: 3.6 mg/dl to 6 mg/dl for women and 3.5 mg/dl to 7 mg/dl for men, Quartile 3: ≥ 6 mg/dl for women and ≥ 7 mg/dl for men. The outcomes were the development of acute kidney injury (AKI) and in-hospital mortality. Results. 146 patients were included in the analysis. The median age of patients was 57 (IQR, 49-65) years and 70.5% were male. The overall median serum uric acid level on admission was 4.4 (IQR, 3.5-5.9) mg/dl. Participants in the highest serum uric acid quartile were significantly more hypertensive, and diabetics and showed significantly higher estimated glomerular filtration rate (eGFR) and troponin T levels compared to patients in the lowest serum uric acid quartile. On the other hand; patients in the lowest serum uric acid quartile were admitted with more severe disease than patients with Quartile 2. During follow-up, 19 (13.1%) participants experienced AKI and 15 (10.3%) died. There were significantly positive correlations between AKI and age, hypertension, serum creatinine (SCr), hyperuricemia, C-reactive protein (CRP) and Troponin T (r=0.263, P=0.001; r=0.192, P=0.02; r=0.182, P=0.028; r=0.235, P = 0.004; r=0.219, P=0.008; r=0.236, P=0.004, respectively). A significantly negative correlation was noted between AKI and eGFR (r=-0.189, P=0.023). According to multivariate logistic regression analysis, AKI development was independently associated with CRP and hyperuricemia (OR, 1.009; 95% CI, 1.0082-1.016, P=0.009 and OR, 4.314; 95% CI, 1.190-15.633, P=0.026). The receiver operating characteristic (ROC) curve showed that the area under the curve (AUC) of the concentration of serum admission uric acid was 0.693 (95% CI 0.537–0.849, P=0.006) and the cutoff value was 5.45 mg/dl (sensitivity: 68.4%; specificity: 75.6%). Conclusions. Hyperuricemia and increased CRP were independent risk factors for the development of AKI. Although patients with lower uric acid values developed more severe symptoms, mechanical ventilation and mortality rates were not found to be significantly different among patients with Covid-19 grouped based on admission serum uric values. Following the patients admitted with high uric acid levels closely in terms of renal functions would be helpful for early detection of AKI.